Mixed neurotransmission in the hippocampal mossy fibers - Muenster-Wandowski, Agnieszka; Gómez-Lira, Gisela; Gutierrez, Rafael (Frontiers in Cellular Neuroscience, 2013)
The hippocampal mossy fibers (MFs), the axons of the granule cells (GCs) of the dentate gyrus, innervate mossy cells and interneurons in the hilus on their way to CA3 where they innervate interneurons and pyramidal cells. Synapses on each target cell have distinct anatomical and functional characteristics. In recent years, the paradigmatic view of the MF synapses being only glutamatergic and, thus, excitatory has been questioned. Several laboratories have provided data supporting the hypothesis that the MFs can transiently release GABA during development and, in the adult, after periods of enhanced excitability. This transient glutamate-GABA co-transmission coincides with the transient up-regulation of the machinery for the synthesis and release of GABA in the glutamatergic GCs. Although some investigators have deemed this evidence controversial, new data has appeared with direct evidence of co-release of glutamate and GABA from single, identified MF boutons. However, this must still be confirmed by other groups and with other methodologies. A second, intriguing observation is that MF activation produced fast spikelets followed by excitatory postsynaptic potentials in a number of pyramidal cells, which, unlike the spikelets, underwent frequency potentiation and were strongly depressed by activation of metabotropic glutamate receptors. The spikelets persisted during blockade of chemical transmission and were suppressed by the gap junction blocker carbenoxolone. These data are consistent with the hypothesis of mixed electrical-chemical synapses between MFs and some pyramidal cells. Dye coupling between these types of principal cells and ultrastructural studies showing the co-existence of AMPA receptors and connexin 36 in this synapse corroborate their presence. A deeper consideration of mixed neurotransmission taking place in this synapse may expand our search and understanding of communication channels between different regions of the mammalian CNS.